Awareness of professional ethics in midwifery - Shaghayegh Majzobi; Hana Sohrabi; Ronak Shahoei; Mahsa Sohrabi (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Professional ethics is defined as ethical commitment and conscience in regards to every profession, duty or responsibility in order to prevent patient harm, which in turn accelerates recovery. The present study aimed to determine the level of knowledge regarding professional ethics and its influential factors among midwives in Sanandaj, Iran in 2017. Materials and Methods: This cross-sectional study was conducted on 150 midwives employed in the hospitals and health centers in Sanandaj city. The subjects were selected via simple random sampling. Data were collected using a two-part questionnaire. The first section consisted of demographic characteristics, and the second section contained data on the knowledge of various aspects of professional ethics. Data analysis was performed in SPSS version 18 using descriptive and inferential statistics at the P-value of less than 0.05. Results: The general knowledge of the majority of the midwives (92%) regarding professional ethics was favorable. In addition, significant associations were observed between marital status (P=0.046), workplace (P=0.010), and interest and motivation (P=0.013) with the general knowledge of professional ethics. Conclusion: According to the results, the midwives employed in the hospitals and health centers in Sanandaj had proper knowledge of professional ethics.